2018
DOI: 10.1101/491225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncovering the role of admixture in disease and drug response: Association of hepatocyte gene expression and DNA methylation with African Ancestry in African Americans

Abstract: BackgroundAfrican Americans (AAs) are an admixed population with portions of their genome derived from West Africans and Europeans. In AAs, the proportion of West African ancestry (WAA) can vary widely and may explain the genetic drivers of disease, specifically those that disproportionately affect this understudied population. To examine the relationship between the proportion of WAA and gene expression, we used high dimensional data obtained from AA primary hepatocytes, a tissue important in disease and drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…We excluded any livers with active cancer or with a history of hepatocarcinoma. Primary hepatocytes were isolated and cultured as previously described in Park et al [54]. The workflow of genotyping QC and RNA sequencing QC is in Fig 1A. Genotyping and imputation DNA was extracted from each hepatocyte line using Gentra Puregene Blood kit (Qiagen).…”
Section: Cohortmentioning
confidence: 99%
“…We excluded any livers with active cancer or with a history of hepatocarcinoma. Primary hepatocytes were isolated and cultured as previously described in Park et al [54]. The workflow of genotyping QC and RNA sequencing QC is in Fig 1A. Genotyping and imputation DNA was extracted from each hepatocyte line using Gentra Puregene Blood kit (Qiagen).…”
Section: Cohortmentioning
confidence: 99%
“…The CYP2C19*17 allele, which is found in African ancestry populations (24%), was associated with an increased 1‐year mortality rate and an increased risk of bleeding in African Americans . A recent study has shown that the proportion of African ancestry may be associated with the hepatic expression on CYP2C19 . Even in genes as important as these, most GWAS of drug response have been conducted in European and Asian populations, leaving the effect of population‐specific variants unknown.…”
Section: Pharmacogenomics and Minority Populationsmentioning
confidence: 99%
“…53 A recent study has shown that the proportion of African ancestry may be associated with the hepatic expression on CYP2C19. 54 Even in genes as important as these, most GWAS of drug response have been conducted in European and Asian populations, leaving the effect of population-specific variants unknown.…”
Section: Cross-population Differences In Drug Responsementioning
confidence: 99%
“…COVID-19 cases and deaths are disproportionately higher among African Americans; this is often attributed to a complex combination of socio-economic factors 15,36,37 . However, a number of studies have shown differences in genes expression among races [38][39][40][41] . Gene expression reflects the interaction between environmental/physiological and genetic influences.…”
Section: Introductionmentioning
confidence: 99%